PELATIHAN DESAIN LOGO DAN KEMASAN UMKM KERIPIK PISANG DESA TRUNAMANGGALA MELALUI PENJUALAN DIGITAL MARKETING - Maulana, Aldilla Rizqy; Kuswandi, Aos (Universitas Islam 45 Bekasi, 2024)
The development of micro, small and medium enterprises aims to generate income for the lower middle class and is the most important driver in the national economy. In an effort to improve the welfare of micro, small and medium enterprises, the government currently offers various programs to business actors, including business capital, training, and business assistance with stakeholders. The banana chip business, which is one form of small micro business in Trunamanggala Village, Cimalaka District, Sumedang Regency, has problems in the form of the absence of a logo as a product identity, the absence of attractive packaging and the lack of utilization of digital marketing technology in its sales so that an assistance is needed to overcome this. Therefore, this community service method uses a training and socialization approach which aims to provide training in making product logos as well as providing training in marketing products online. The positive impact of this training is to increase market attractiveness and interest to help product images with creative logos, MSME players have products in digital marketing so that they can increase promotion of banana chip MSME players and increase the economy and profits for banana chip MSME players in Trunamanggala Village.